Production formula and detection method of fiber pressure-bearing plugging agent

By using fiber pressure-bearing sealing agent composed of ultrafine polypropylene fibers and other materials, the problem of existing leak-blocking agent sealing doors when encountering water is solved, and an efficient and stable well leakage sealing effect is achieved.

CN119463831APending Publication Date: 2025-02-18DONGYING NEW IDEA PETROLEUM TECH SERVICE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411613675.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing bridge plug-ins are prone to seal the door when exposed to water, resulting in failure of leakage and inability to effectively seal the well leakage.

Method used

The fiber pressure-bearing sealing agent consists of ultrafine polypropylene fiber, water-mestone fiber, jujube shell, mica sheet No. 1, ultrafine calcium carbonate, rubber particles, calcium carbonate particles, soil powder and polymer 3860. The combination of high-strength engineered fibers and easily wet materials achieves uniform dispersion and effective sealing of materials.

Benefits of technology

This product can effectively block the severe loss of 5 mm cracks, has a significant leakage plugging effect, and can show an effective intrusion depth greater than 15 cm in multiple formation loss simulation tests, and a pressure bearing capacity greater than 5 MPa. Press for 30 minutes without re-discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of fiber pressure-bearing plugging, in particular to a production formula and a detection method of a fiber pressure-bearing plugging agent, and the fiber pressure-bearing plugging agent comprises the following basic components: superfine polypropylene fiber, Shuimei fiber, wild jujube shell, No.1 mica sheet, superfine calcium carbonate, rubber particles, calcium carbonate particles, soil powder and a polymer 3860. The pressure-bearing plugging agent with a spatial three-dimensional structure, which is formed by taking superfine engineering fibers as a main body and dozens of materials with different shapes and particle sizes as auxiliary materials, is simple and convenient to operate, can effectively plug serious loss of cracks of 5mm and has a remarkable plugging effect; according to the present invention, other materials with easily-infiltrated surfaces are adopted to replace sawdust and the like, and other fibers and pressure-resistant and temperature-resistant filling materials are added so as to achieve the uniform dispersion during the preparation of the plugging agent, and achieve the effects of entering, standing and not exiting in the plugging process so as to achieve the successful plugging;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber pressure-bearing plugging, and specifically to a production formula and detection method of a fiber pressure-bearing plugging agent. Background Art

[0002] The occurrence of well leakage brings great difficulties to the exploration and development of oil and gas resources. When well leakage occurs, the staff needs to use bridge plugs to plug the leakage layer in time.

[0003] However, existing bridge plug plugging agents basically use cottonseed husk as the main plugging fiber, walnut shell as the bridging material, and sawdust, clam shell residue, etc. as filling materials. These materials are basically hydrophobic and difficult to disperse evenly in the drilling fluid. In particular, cottonseed husk clumps when it meets water, which is very easy to block during the plugging process, making it impossible for the plugging agent to enter the leak point, resulting in plugging failure. Summary of the invention

[0004] The purpose of the invention is to provide a production formula and detection method of a fiber pressure-bearing plugging agent to solve the problem of easy door sealing during the plugging process mentioned in the above background technology.

[0005] To achieve the above purpose, the invention provides the following technical solutions: a production formula and a detection method of a fiber pressure-bearing plugging agent, comprising:

[0006] The basic components of the fiber pressure plugging agent are ultrafine polypropylene fiber, water-melt stone fiber, sour jujube shell, No. 1 mica flakes, ultrafine calcium carbonate, rubber particles, calcium carbonate particles, soil powder and polymer 3860;

[0007] The test reagents and materials include: deionized water, bentonite for drilling fluid test slurry, anhydrous sodium carbonate, hydrochloric acid, silver nitrate, xanthan gum, river sand, sodium hydroxide, apricot kernel peel, No. 2 mica flakes, broad pH test paper and silicone defoamer;

[0008] The inspection instruments and equipment include: electronic balance, constant temperature drying oven, high-speed stirrer, leak plugging instrument, G2 glass sand core crucible and high temperature and high pressure filter loss instrument.

[0009] Preferably, the size specification length requirement of the ultrafine polypropylene fiber is 3 to 8 mm, and specifically 3 mm, 6 mm and 8 mm, and the size specification length requirement of the sour jujube shell is 1 to 4 mm, and specifically 1 mm, 2 mm, 3 mm and 4 mm.

[0010] Preferably, the size specification requirement of the No. 1 mica sheet is 2 mm, the size specification requirement of the ultrafine calcium carbonate is 800-1500 mesh, and specifically 800 mesh and 1500 mesh, and the size specification requirement of the rubber particles is 20 mesh.

[0011] Preferably, the size specification requirement of the calcium carbonate particles is 60 mesh, the soil powder is required to be first-grade sodium soil, the deionized water should comply with the requirements of GB / T 6682-2008 for third-grade water, the bentonite used for drilling fluid test slurry should comply with the provisions of SY / T5490-2016, and the hydrochloric acid and deionized water are prepared into a 1:1 solution.

[0012] Preferably, the silver nitrate and deionized water are mixed into a 1% solution, the xanthan gum should meet the requirements of GB / T 5005-2010, the size specification of the river sand is required to be 0.42mm-0.84mm, i.e. 20 mesh-40 mesh, and it needs to be dried at 105°C±2°C for 4 hours and then cooled in a dryer for use.

[0013] Preferably, the particle size of the apricot kernel peel is required to be 1mm to 2mm, the particle size of the No. 2 mica sheet is required to be 1mm to 2mm, the accuracy of the electronic balance is 0.01g; the precision is 0.0001g, the temperature range of the constant temperature drying oven is 200°C, and the temperature control sensitivity is ±2°C.

[0014] Preferably, the load speed of the high-speed agitator is 11000r / min±300r / min, the rotating shaft should be equipped with a single sinusoidal blade with a diameter of about 25mm, the stamping surface is installed upward and matched with a high stirring cup, the leak plugging instrument is QD-2 type or similar products and matched with 2mm, 3mm, 5mm disc seam plates, and the high-temperature and high-pressure filtration instrument is GGS71-A type or similar products.

[0015] Compared with the prior art, the invention has the following beneficial effects: the product is a pressure-bearing plugging agent with a three-dimensional structure, which is mainly composed of ultrafine engineering fibers and dozens of materials of different shapes and particle sizes as auxiliary materials. The product is a bag-type plugging agent, which can be directly prepared by adding water at the construction site. The operation is simple and convenient, and it can effectively plug the serious leakage of 5 mm cracks. After multiple evaluations by the formation leakage simulation tester, the effective invasion depth is greater than 15 cm, the pressure bearing capacity is greater than 5 MPa, the pressure is stabilized for 30 minutes, and there is no backflow phenomenon at a pressure of 4 MPa, and the plugging effect is significant.

[0016] This product uses high-strength engineering fibers to replace cottonseed husks, and other easily wetted materials to replace sawdust, and at the same time adds other fibers and pressure-resistant and temperature-resistant filling materials to ensure that the plugging agent can be evenly dispersed when prepared. During the plugging process, it can achieve the effect of "being able to enter, stand, and not come out", thereby achieving successful plugging. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments of the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.

[0018] An embodiment provided by the invention: a production formula and a detection method of a fiber pressure-bearing plugging agent, comprising:

[0019] The basic components of the fiber pressure plugging agent are ultrafine polypropylene fiber, water-melting stone fiber, sour jujube shell, No. 1 mica flakes, ultrafine calcium carbonate, rubber particles, calcium carbonate particles, soil powder and polymer 3860. Ultrafine calcium carbonate is a classification of calcium carbonate.

[0020] The test reagents and materials include: deionized water, bentonite for drilling fluid test slurry, anhydrous sodium carbonate, hydrochloric acid, silver nitrate, xanthan gum, river sand, sodium hydroxide, apricot kernel peel, No. 2 mica flakes, broad pH test paper and silicone defoamer. The mica flakes are composed of polysilicon muscovite, quartz, garnet and rutile;

[0021] The inspection instruments and equipment include: electronic balance, constant temperature drying oven, high-speed stirrer, leak plugging instrument, G2 glass sand core crucible and high-temperature and high-pressure filter loss instrument. The high-temperature and high-pressure filter loss instrument is an instrument that simulates deep wells under high temperature and high pressure conditions to test the filter loss of drilling fluid or cement slurry.

[0022] Furthermore, the size specification of ultrafine polypropylene fiber is required to be 3 to 8 mm in length, and specifically 3 mm, 6 mm and 8 mm. Polypropylene fiber is a synthetic fiber spun from isotactic polypropylene obtained by polymerization of propylene. The size specification of sour jujube shell is required to be 1 to 4 mm, and specifically 1 mm, 2 mm, 3 mm and 4 mm.

[0023] Furthermore, the size specification requirement of No. 1 mica flakes is 2mm, the size specification requirement of ultrafine calcium carbonate is 800-1500 mesh, and specifically 800 mesh and 1500 mesh. Ultrafine calcium carbonate is a classification of calcium carbonate, and the size specification requirement of rubber particles is 20 mesh.

[0024] Furthermore, the size specification of calcium carbonate particles is required to be 60 mesh, the soil powder is required to be first-grade sodium soil, the deionized water should comply with the requirements of GB / T 6682-2008 for third-grade water, the bentonite used for drilling fluid test slurry should comply with the provisions of SY / T 5490-2016, and hydrochloric acid and deionized water are prepared into a 1:1 solution. Calcium carbonate is an inorganic compound and is the main component of limestone, marble, etc. Calcium carbonate is usually white crystals, odorless, basically insoluble in water, and easily reacts with acid to release carbon dioxide.

[0025] Furthermore, silver nitrate is mixed with deionized water to form a 1% solution. Xanthan gum should meet the requirements of GB / T5005-2010. The size of river sand is required to be 0.42mm~0.84mm, i.e. 20 mesh~40 mesh. It needs to be dried at 105℃±2℃ for 4h and then cooled in a dryer for use. Xanthan gum is a widely used microbial extracellular polysaccharide produced by fermentation engineering of Xanthomonas campestris using carbohydrates as the main raw material.

[0026] Furthermore, the particle size of apricot kernel peel is required to be 1mm~2mm, the particle size of No. 2 mica sheet is required to be 1mm~2mm, the accuracy of the electronic balance is 0.01g; the accuracy is 0.0001g, the temperature range of the constant temperature drying oven is 200℃, the temperature control sensitivity is ±2℃, and the mica sheet is composed of polysilicon muscovite, quartz, garnet and rutile.

[0027] Furthermore, the load speed of the high-speed agitator is 11000r / min±300r / min, the rotating shaft should be equipped with a single sinusoidal blade with a diameter of about 25mm, the stamping surface is installed upward and matched with a high stirring cup, the leak plugging instrument is QD-2 type or similar products and matched with 2mm, 3mm, 5mm disc seam plates, the high-temperature and high-pressure filter loss meter is GGS71-A type or similar products, and the high-temperature and high-pressure filter loss meter is an instrument that simulates deep wells under high temperature and high pressure conditions to test the filter loss of drilling fluid or cement slurry.

[0028] Moisture determination:

[0029] Weigh the mass of a clean and dry weighing bottle (accurate to 0.0001g), recorded as m1. Add 2g (accurate to 0.0001g) of sample to the weighing bottle, weigh its total mass, recorded as m2. Place the weighing bottle containing the sample in a 105℃ constant temperature drying oven and dry it at constant temperature for 2h. After taking it out, place it in a desiccator, cool it to room temperature, and weigh its total mass (accurate to 0.0001g), recorded as m3. Calculate the water content according to formula (1).

[0030]

[0031] Where:

[0032] W—water content, %;

[0033] m1 - weight of weighing bottle, g;

[0034] m2-the mass of the weighing bottle and the sample before drying, g;

[0035] m3-the mass of the sample added to the weighing bottle after drying, g.

[0036] XSLC-Ⅰ plugging liquid was prepared from ultrafine polypropylene fiber (3 mm in length), hydrophilic stone fiber, jujube shell (1-2 mm), No. 1 mica flakes (2 mm), ultrafine calcium carbonate (800 mesh, 1500 mesh), rubber particles (20 mesh), calcium carbonate particles (60 mesh), soil powder (first-grade sodium soil) and polymer 3860;

[0037] XSLC-II plugging liquid was prepared from ultrafine polypropylene fiber (6 mm, 3 mm in length), hydrophilic stone fiber, sour jujube shell (3 mm), No. 1 mica flakes (2 mm), ultrafine calcium carbonate (800 mesh, 1500 mesh), rubber particles (20 mesh), calcium carbonate particles (60 mesh), soil powder (first-grade sodium soil) and polymer 3860;

[0038] XSLC-Ⅲ plugging liquid is made of ultrafine polypropylene fiber (length 8 mm, 6 mm), water-melt stone fiber, jujube shell (3-4 mm), No. 1 mica sheet (2 mm), ultrafine calcium carbonate (800 mesh, 1500 mesh), rubber particles (20 mesh), calcium carbonate particles (60 mesh), soil powder (first-grade sodium soil) and polymer 3860.

[0039] Seam plate pressure bearing capacity:

[0040] XSLC-Ⅰ detection method:

[0041] a) Sealing fluid: Measure 500 mL of deionized water into a high-stirring cup, add 30.00 g (accurate to 0.01 g) of bentonite for slurry preparation and 1.05 g (accurate to 0.01 g) of anhydrous sodium carbonate in sequence while stirring at a speed of 11000 r / min. Stir for a total of 20 min and cure at room temperature for 24 h for use.

[0042] b) XSLC-Ⅰ series plugging liquid: Measure 400mL of deionized water into three high-stirring cups respectively, add 70.00g of sample while stirring at a speed of 11000r / min, and continue stirring for 3min for use.

[0043] c) Test method: Install a 2mm seam plate on the inner step of the ball valve joint of the QD-2 plugging instrument, tighten the outlet elbow, open the ball valve, and place a liquid receiving container under the outlet. With the outlet ball valve of the plugging device open, inject XSLC-Ⅰ plugging liquid into the device, tighten the device cover, and connect the pressure source. Start the stopwatch to apply pressure at a uniform speed, reach 0.7MPa within 50s and maintain this pressure until the deionized water in the XW-1 plugging liquid is drained, turn off the gas source switch after 2 minutes of gas release, and let the pressure in the device automatically drop to zero. Reopen the cover of the device, add 500ml of sealing fluid, tighten the cover, and connect the gas source; increase the pressure at a uniform rate, first add 1MPa, stabilize the pressure for 3min, then slowly increase the pressure, increase 1MPa every 3 minutes, and finally increase the pressure to 5MPa and stop pressurizing. After reaching 5MPa, turn off the gas source switch and start timing and measuring the filtration loss. If this pressure can be maintained for 10min without pressure drop and the filtration loss is less than 500mL, the pressure bearing capacity is qualified.

[0044] XSLC-Ⅱ detection method:

[0045] a) Sealing fluid: Measure 500 mL of deionized water into a high-stirring cup, add 30.00 g (accurate to 0.01 g) of bentonite for slurry preparation and 1.05 g (accurate to 0.01 g) of anhydrous sodium carbonate in sequence while stirring at a speed of 11000 r / min. Stir for a total of 20 min and cure at room temperature for 24 h for use.

[0046] b) XSLC-Ⅱ series plugging liquid: Measure 400mL of deionized water into three high-stirring cups respectively, add 70.00g of sample while stirring at a speed of 11000r / min, and continue stirring for 3min for use.

[0047] c) Test method: Install the 3mm seam plate on the inner step of the ball valve joint of the QD-2 plugging instrument, tighten the outlet elbow, open the ball valve, and place a liquid receiving container under the outlet. With the outlet ball valve of the plugging device open, inject XSLC-Ⅱ plugging liquid into the device, tighten the device cover, and connect the pressure source. Start the stopwatch to apply pressure at a uniform speed, reach 0.7MPa within 50s and maintain this pressure until the deionized water in the XW-1 plugging liquid is drained, turn off the gas source switch after 2 minutes of gas release, and let the pressure in the device automatically drop to zero. Reopen the cover of the device, add 500ml of sealing fluid, tighten the cover, and connect the gas source; increase the pressure at a uniform rate, first add 1MPa, stabilize the pressure for 3min, then slowly increase the pressure, increase 1MPa every 3 minutes, and finally increase the pressure to 5MPa and stop pressurizing. After reaching 5MPa, turn off the gas source switch and start timing and measuring the filtration loss. If this pressure can be maintained for 10min without pressure drop, and the filtration loss is less than 700mL, the pressure bearing capacity is qualified.

[0048] XSLC-Ⅲ detection method:

[0049] a) Sealing fluid: Measure 500 mL of deionized water into a high-stirring cup, add 30.00 g (accurate to 0.01 g) of bentonite for slurry preparation and 1.05 g (accurate to 0.01 g) of anhydrous sodium carbonate in sequence while stirring at a speed of 11000 r / min. Stir for a total of 20 min and cure at room temperature for 24 h for use.

[0050] b) XSLC-Ⅲ series plugging liquid: Measure 400mL of deionized water into three high-stirring cups respectively, add 70.00g of sample while stirring at a speed of 11000r / min, and continue stirring for 3min for use.

[0051] c) Test method: Install the 3mm seam plate on the inner step of the ball valve joint of the QD-2 plugging instrument, tighten the outlet elbow, open the ball valve, and place a liquid receiving container under the outlet. With the outlet ball valve of the plugging device open, inject XSLC-Ⅲ plugging liquid into the device, tighten the device cover, and connect the pressure source. Start the stopwatch to apply pressure at a uniform speed, reach 0.7MPa within 50s and maintain this pressure until the deionized water in the XW-1 plugging liquid is drained, turn off the gas source switch after 2min of gas release, and let the pressure in the device automatically drop to zero. Reopen the cover of the device, add 500ml of sealing fluid, tighten the cover, and connect the gas source; increase the pressure at a uniform rate, first add 1MPa, stabilize the pressure for 3min, then slowly increase the pressure, increase 1MPa every 3 minutes, and finally increase the pressure to 5MPa and stop pressurizing. After reaching 5MPa, turn off the gas source switch and start timing and measuring the filtration loss. If this pressure can be maintained for 10min without pressure drop, and the filtration loss is less than 800mL, the pressure bearing capacity is qualified.

[0052] Pressure loss (sand bed, 5.0Mpa)

[0053] Sample slurry preparation

[0054] Take 400ml of distilled water, add 0.40g (accurate to 0.01g) of sodium hydroxide at 11000r / min using a high-speed stirrer, stir for 5min, adjust the pH value to 9-10, add 16.00g (accurate to 0.01g) of XSLC plugging agent sample, stir for 10min, add 1.60g (accurate to 0.01g) of xanthan gum, stir for 30min. Stop twice within the above fixed time to scrape off the adherents on the cup wall, and add two drops of silicone defoamer after stirring.

[0055] Sand bed pressure bearing capacity

[0056] Use GGS71-A high-temperature and high-pressure filtration meter. Add filter screen only without adding filter paper to the drilling fluid cup. Add 500g of 20-40 mesh dry and clean river sand. When the lower ventilation valve stem is open, use a small iron rod to insert and compact the river sand. Use a glass rod to drain the sample slurry in 4.3.3.1 and slowly add 150ml to the high-temperature and high-pressure drilling fluid cup. Install the cup cover, open the upper valve stem and slowly pressurize to 0.7MPa, stabilize the pressure for 10min, then slowly and evenly pressurize to 5.0MPa and start measuring the filtration loss, stabilize the pressure for 30min.

[0057] a If the filtration loss of XSLC-Ⅰ is less than 80mL, the pressure bearing capacity is qualified.

[0058] b If the filtration loss of XSLC-Ⅱ is less than 100mL, the pressure bearing capacity is qualified.

[0059] c If the filtration loss of XSLC-Ⅲ is less than 110mL, the pressure bearing capacity is qualified.

[0060] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-restrictive, and the scope of the invention is defined by the appended claims rather than the above description, and it is intended that all changes within the meaning and range of equivalents of the claims be included in the invention. Any sign in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A production formula and detection method of a fiber pressure-bearing plugging agent, characterized in that: include, The basic components of the fiber pressure plugging agent are ultrafine polypropylene fiber, water-melt stone fiber, sour jujube shell, No. 1 mica flakes, ultrafine calcium carbonate, rubber particles, calcium carbonate particles, soil powder and polymer 3860; The test reagents and materials include: deionized water, bentonite for drilling fluid test slurry, anhydrous sodium carbonate, hydrochloric acid, silver nitrate, xanthan gum, river sand, sodium hydroxide, apricot kernel peel, No. 2 mica flakes, broad pH test paper and silicone defoamer; The inspection instruments and equipment include: electronic balance, constant temperature drying oven, high-speed stirrer, leak plugging instrument, G2 glass sand core crucible and high temperature and high pressure filter loss instrument.

2. The production formula and detection method of a fiber pressure-bearing plugging agent according to claim 1, characterized in that: The size specification length requirement of the ultrafine polypropylene fiber is 3 to 8 mm, and specifically 3 mm, 6 mm and 8 mm. The size specification length requirement of the sour jujube shell is 1 to 4 mm, and specifically 1 mm, 2 mm, 3 mm and 4 mm.

3. The production formula and detection method of a fiber pressure-bearing plugging agent according to claim 1, characterized in that: The size specification requirement of the No. 1 mica sheet is 2 mm, the size specification requirement of the ultrafine calcium carbonate is 800-1500 mesh, and specifically 800 mesh and 1500 mesh, and the size specification requirement of the rubber particles is 20 mesh.

4. The production formula and detection method of a fiber pressure-bearing plugging agent according to claim 1, characterized in that: The size specification requirement of the calcium carbonate particles is 60 mesh, the soil powder is required to be first-grade sodium soil, the deionized water should comply with the requirements of GB / T 6682-2008 third-grade water, the bentonite used for drilling fluid test slurry should comply with the provisions of SY / T 5490-2016, and the hydrochloric acid and deionized water are prepared into a 1:1 solution.

5. The production formula and detection method of a fiber pressure-bearing plugging agent according to claim 2, characterized in that: The silver nitrate and deionized water are mixed into a 1% solution, the xanthan gum should meet the requirements of GB / T 5005-2010, the size specification of the river sand is required to be 0.42mm-0.84mm, i.e. 20 mesh-40 mesh, and it needs to be dried at 105°C±2°C for 4 hours and then cooled in a dryer for use.

6. The production formula and detection method of a fiber pressure-bearing plugging agent according to claim 3, characterized in that: The particle size of the apricot kernel peel is required to be 1mm~2mm, the particle size of the No. 2 mica sheet is required to be 1mm~2mm, the accuracy of the electronic balance is 0.01g; the precision is 0.0001g, the temperature range of the constant temperature drying oven is 200℃, and the temperature control sensitivity is ±2℃.

7. The production formula and detection method of a fiber pressure-bearing plugging agent according to claim 4, characterized in that: The load speed of the high-speed agitator is 11000r / min±300r / min. The rotating shaft should be equipped with a single sinusoidal blade with a diameter of about 25mm. The stamping surface is installed upward and is equipped with a high stirring cup. The leak plugging instrument is QD-2 type or similar products and is equipped with 2mm, 3mm, and 5mm disc seam plates. The high-temperature and high-pressure filtration instrument is GGS71-A type or similar products.